Art, Identity, and Social Justice - David, Emmanuel A. (Social justice, 2007)
A special issue on the relationship between art, identity, and social justice is presented. Articles discuss art as a vehicle of social justice; employing the arts in social inquiry with poor, working-class women; the women artists' cooperative space as a site for social change; feminist artists in Mexico; hybridity as a strategy for self-determination in contemporary American Indian art; art, politics, and community in the Bahamas; New York City performing artists as cultural workers; hip-hop art, gay rappers, and social change; and postcards during the rule of Mexican dictator Porfirio Díaz from 1877 to 1911.